2021
DOI: 10.1038/s43856-021-00044-w
|View full text |Cite
|
Sign up to set email alerts
|

Direct SARS-CoV-2 infection of the human inner ear may underlie COVID-19-associated audiovestibular dysfunction

Abstract: Background COVID-19 is a pandemic respiratory and vascular disease caused by SARS-CoV-2 virus. There is a growing number of sensory deficits associated with COVID-19 and molecular mechanisms underlying these deficits are incompletely understood. Methods We report a series of ten COVID-19 patients with audiovestibular symptoms such as hearing loss, vestibular dysfunction and tinnitus. To investigate the causal relationship between SARS-CoV-2 and aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 47 publications
2
86
0
Order By: Relevance
“…The pathogenesis for these findings might be explained by the finding of a unique injury of SARS-CoV-2 of cerebral blood vessels [33] using the viral protease, Mpro, which causes endothelial brain cell death. Another research raised the possibility of direct nerve damage as a basis for audio-vestibular injury following SARS-CoV-2 infection [34].…”
Section: Possible Long-term Sequelae Of Covid-19mentioning
confidence: 99%
“…The pathogenesis for these findings might be explained by the finding of a unique injury of SARS-CoV-2 of cerebral blood vessels [33] using the viral protease, Mpro, which causes endothelial brain cell death. Another research raised the possibility of direct nerve damage as a basis for audio-vestibular injury following SARS-CoV-2 infection [34].…”
Section: Possible Long-term Sequelae Of Covid-19mentioning
confidence: 99%
“…It is well-established that some viral infections cause hearing loss ( 3 ), and it has been found that SARS-CoV-2 can infect the inner ear ( 4 ). This awareness is reflected in the COVID-19 guidelines from the UK National Institute for Health and Care Excellence ( 5 ), which reports that tinnitus, an audiovestibular symptom, can be a common ongoing complaint after COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss and tinnitus are also known rare side effects of COVID-19. A case study involved a series of ten COVID-19 patients who suffered from audiovestibular symptoms such as hearing loss, vestibular dysfunction and tinnitus [185]. The authors demonstrated that human inner ear tissue expresses ACE2, furin and the transmembrane protease serine 2 (TMPRSS2), which facilitates viral entry.…”
Section: Guillain Barré Syndrome and Other Neurological Conditionsmentioning
confidence: 99%